Aquatic environmental DNA: A review of the macro-organismal biomonitoring revolution - Takahashi, Miwa; Saccò, Mattia; Kestel, Joshua H.; Nester, Georgia; Campbell, Matthew A.; van der Heyde, Mieke; Heydenrych, Matthew J.; Juszkiewicz, David J.; Nevill, Paul; Dawkins, Kathryn L.; Bessey, Cindy; Fernandes, Kristen; et al. (The Science of the total environment, 2023)
Environmental DNA (eDNA) is the fastest growing biomonitoring tool fuelled by two key features: time efficiency and sensitivity. Technological advancements allow rapid biodiversity detection at both species and community levels with increasing accuracy. Concurrently, there has been a global demand to standardise eDNA methods, but this is only possible with an in-depth overview of the technological advancements and a discussion of the pros and cons of available methods. We therefore conducted a systematic literature review of 407 peer-reviewed papers on aquatic eDNA published between 2012 and 2021. We observed a gradual increase in the annual number of publications from four (2012) to 28 (2018), followed by a rapid growth to 124 publications in 2021. This was mirrored by a tremendous diversification of methods in all aspects of the eDNA workflow. For example, in 2012 only freezing was applied to preserve filter samples, whereas we recorded 12 different preservation methods in the 2021 literature. Despite an ongoing standardisation debate in the eDNA community, the field is seemingly moving fast in the opposite direction and we discuss the reasons and implications. Moreover, by compiling the largest PCR-primer database to date, we provide information on 522 and 141 published species-specific and metabarcoding primers targeting a wide range of aquatic organisms. This works as a user-friendly ‘distillation’ of primer information that was hitherto scattered across hundreds of papers, but the list also reflects which taxa are commonly studied with eDNA technology in aquatic environments such as fish and amphibians, and reveals that groups such as corals, plankton and algae are under-studied. Efforts to improve sampling and extraction methods, primer specificity and reference databases are crucial to capture these ecologically important taxa in future eDNA biomonitoring surveys. In a rapidly diversifying field, this review synthetises aquatic eDNA procedures and can guide eDNA users towards best practice. [Display omitted] •407 manuscripts were reviewed to examine the last decade of aquatic eDNA research.•Temporal trends in methods, major achievements, and knowledge gaps are identified.•Despite attempt to standardise protocols, eDNA is becoming more method-diverse.•We propose 17 key considerations to guide eDNA study design and method selection.•We compile a list of 663 PCR primers with relevance for aquatic eDNA research.